EMG extractor and blink detection for human health monitoring - Jha, Aanchal; Kumar, M. Ganesh Lakshamana (International Journal of Engineering and Technology, 2018)
In this paper we have proposed noise free EMG extractor for biomedical applications and also provide method for detecting blink signal. EMG signal is applied to preamplifier followed by Chebyshev filter and programmable gain amplifier further this processed EMG signal is applied to comparator to detect the blink. This topology is designed in UMC 180nm CMOS technology. Amplifier with gain of 81.155 dB and CMRR of 155.197 dB is designed. Preamplifier gain of 32.1244 dB with CMRR of 76.0743 dB which leads to common mode cancellation at priliminary stage. It also provide input referred noise ranges from 90 to 101.8636 Âµ V/sqrt(Hz) to reduce the noise for overall system. 4th order Chebyshev filter provides filtering with slope of -80 dB/decade with leads to reduce the unwanted signals. Filtered EMG signal is applied to programmable gain amplifier where gain ranges from 0 to 23 dB.It consumes power of 0.3Âµ W at 1V supply voltage.